Piezoelectric Materials for Energy Harvesting and Sensing Applications: Roadmap for Future Smart Materials - Mahapatra, Susmriti Das; Mohapatra, Preetam Chandan; Aria, Adrianus Indrat; Christie, Graham; Mishra, Yogendra Kumar; Hofmann, Stephan; Thakur, Vijay Kumar (Advanced science, 2021)
Piezoelectric materials are widely referred to as “smart” materials because they can transduce mechanical pressure acting on them to electrical signals and vice versa. They are extensively utilized in harvesting mechanical energy from vibrations, human motion, mechanical loads, etc., and converting them into electrical energy for low power devices. Piezoelectric transduction offers high scalability, simple device designs, and high‐power densities compared to electro‐magnetic/static and triboelectric transducers. This review aims to give a holistic overview of recent developments in piezoelectric nanostructured materials, polymers, polymer nanocomposites, and piezoelectric films for implementation in energy harvesting. The progress in fabrication techniques, morphology, piezoelectric properties, energy harvesting performance, and underpinning fundamental mechanisms for each class of materials, including polymer nanocomposites using conducting, non‐conducting, and hybrid fillers are discussed. The emergent application horizon of piezoelectric energy harvesters particularly for wireless devices and self‐powered sensors is highlighted, and the current challenges and future prospects are critically discussed. This paper presents a comprehensive review of the energy harvesting performance of different types of piezoelectric materials. These materials include nanostructured materials, polymers, polymer nanocomposites synthesized using different types of fillers and piezoelectric films. The fabrication techniques, energy harvesting mechanisms, and applications of piezoelectric nanogenerators built using these materials are discussed thoroughly.